Chemo‐mechanical polish lithography: A pathway to low loss large‐scale photonic integration on lithium niobate on insulator. Issue 1 (28th March 2019) - Wang, Min; Wu, Rongbo; Lin, Jintian; Zhang, Jianhao; Fang, Zhiwei; Chai, Zhifang; Cheng, Ya
Summary: We discuss the recent breakthrough in the field of photonic integrated circuits for generating high‐quality photonic structures on lithium niobate (LN) on insulator (LNOI). This is enabled by the development of chemo‐mechanical polish lithography (CMPL). We begin with a brief introduction of the background, followed by the description of the CMPL technique that holds the promise for realizing LNOI waveguides of ultralow propagation loss approaching the absorption limit of LN. We demonstrate fabrication of low loss optical waveguides with the CMPL and construction of beamsplitters with the fabricated LNOI waveguides. At last, some conclusions and future perspectives will be given. A video abstract of this article can be found at:https://youtu.be/sgnecU_QzcY